Foreign bodies: Be/longing and gender in the short fiction of Dorothy Allison - Meisel, Jacqueline (The International Journal of the Humanities: Annual Review, 2010)
Which comes first, the body or the word? Food or sex; affect or ideas? Taking Judith Butler’s contention that the body is discursively constructed, this paper will examine the relationship between language and corporeality in Dorothy Allison’s story “A Lesbian Appetite.” Allison, a writer who interrogatesracial and sexual identitiesin the American South, offers a particularly significant treatment of this dynamic by placing the physical body and discursively produced lesbian subjects at the center of her story. As critic Christina Jarvis puts it, this story “provides a useful intervention within recent queer theory, offering sexual identities that are performative as well as attentive to the specificities of race, class, sex, ethnicity, and the body” (2000) and regional cuisine. This paper will examine the liminal subjectivities of the discursive and corporeal body, racial and gendered. While there is in the postmodern approach a powerful sense of indeterminacy in literature and life, there is another force requiring that we acknowledge the corporeality of the body, the “real,” materiality. It argues for the transformative integration of theory and practice, materialist feminism informed by a postmodern consciousness as applied to Allison’s work. Here, language constructs the possibility of change
Keywords: amériques; approches et analyses; corps; féminisme matérialiste; genre; queer; ressource en ligne; régions géographiques; sexualité; thématiques; états-unis